Book Of Papers: XV Simpósio Nacional de Sistemas Prediais: [SISPRED 2023] - Kalbusch, Andreza; Prado Abreu Reis, Ricardo; Martins de Paula, Heber (SIMPÓSIO NACIONAL DE SISTEMAS PREDIAIS, 2023)
Book Of Papers: XV Simpósio Nacional de Sistemas Prediais